Kpi for students satisfaction measurement as an indicator of university management - Izquierdo-Yusta, Alicia; Jiménez-Zarco, Ana Isabel; González-González, Inés; Gómez-Cantó, Carmen M (Journal of Management and Business Education, 2020)
Currently universities need to be competitive. The current environment forces universities to design strategies where the student becomes the center of their activity. Elements such as student satisfaction become key performance indicators of the strategy, so that universities are required to establish metrics that make it possible to measure the level of performance achieved based on the objectives they had previously set. In order to verify it, through a series of dimensions that measure the satisfaction of the teaching-learning process, a scale has been proposed to measure satisfaction. To confirm the consistency of the proposed scale, the reliability and validity indicators of the same were verified. The selected sample corresponds to university students studying undergraduate and master’s degrees in the online mode. Results obtained show the importance of correctly setting the objectives and contents of the different subjects that make up the curricula of each grade, as well as the outstanding role that the teacher has in said process.